“What if a Person Gets the Vaccine and Turns into an Alligator?”: A Study of the Effect of Ideological Polarization on Purchase Intention - Eduardo Mesquita; Evandro Luiz Lopes; Eliane Herrero (BBR: Brazilian Business Review)
In this study, the main objective is to identify the effect of ideological polarization on the generation of both hate and purchase intent (PI), in relation to a brand. A survey encouraged 206 participants to think that a significant brand would support a political candidate antagonistic to their personal beliefs. We identified the political ideology declared and then measured the hatred generated in this situation, in addition to the regulatory focus (preventive versus promotional), and PI in relation to the brand. The results showed the relationship between the participant’s ideological polarization (right-wing or left-wing) and the PI. We also identified that involvement and brand hate - as generated by a non-congruent positioning between the brand and the ideological respondent - ​​mediated the relationship between self-congruence and PI. Additionally, regulatory focus moderated the effects of the relationships among involvement and brand hate and the PI.